Applicability of taxonomic sufficiency of macrofaunal assemblages in benthic ecological quality assessments: Insights from a semi-enclosed bay - Liu, Jiawei; Xu, Zhaodong; Liu, Xiaoshou (Frontiers in Marine Science, 2023)
To explore the applicability of taxonomic sufficiency in benthic ecological quality assessments, we analyzed the similarity of data matrices under different taxonomic levels and transformations based on macrofaunal data sampled from a semi-enclosed bay. The data matrix similarity revealed a highly significant correlation among the similarity matrices at the species level and those at the higher taxonomic levels (genus, family and order), while the correlation coefficients among the matrices decreased with increasing taxonomic levels. Second-stage CLUSTER plots showed that the quantitative genus level was the closest to the quantitative species level. The loss of family level data varied among seasons. The results of the response to environmental factors at the genus and family levels were similar to those at the species level. In the assessment of the benthic ecological quality of semi-enclosed bays, the level of macrofauna identification can be at the genus or family level to improve the cost performance, depending on logistical conditions.